Peran Pejabat Eksekutif sebagai Pelaksana Fungsi Kepatuhan dalam Penerapan Prinsip Good Corporate Governance pada PT. BPR Gunung Simping Artha Purwokerto - Dicky Jaya Mahendra; Edith Ratna (Universitas Batanghari Jambi, 2023)
Executive officers are officials who are elected to carry out compliance duties in the company, especially in rural banks, and are directly responsible to the Director. Carrying out tasks is very important for BPR so that the work program complies with applicable regulations. Based on the Financial Services Authority Regulation Number 4/POJK.03/2015 Implementation regarding Governance for Rural Banks, it is stated that the work unit or executive officer assigned to ensure company compliance must carry out management related to compliance with regulations, and then report it to Director. In this study, the company PT. will be specific. BPR Gunung Simping Artha Purwokerto has carried out its compliance duties by appointing executives who are proven through the submitted Good Corporate Governance reports, which reflect the principle of accountability.